The Effect of Weight Gain on Recurrence During Hormonal Therapy in Breast Cancer with Positive Estrogen Receptor and Negative Her2 Subtype - Nugraha, Doddy Rizqi; Taroeno-Hariadi, Kartika Widayati; Hardianti, Mardiah Suci (Faculty of Medicine Universitas Gadjah Mada, 2021)
Background. Weight gain is found in patients with positive estrogen subtype breast cancer. The effect of weight gain on breast cancer recurrence is still being debated and associated with a poor prognosis. Being overweight is associated with an increase in estrogen production by adipose tissue.Methods. A retrospective and prospective cohort study with data collection was conducted from July 2018 - June 2019 at the outpatient unit of Dr. Sardjito Hospital. We reviewed medical records of patients who came from January 2013 - July 2018. Three categories of weight gain: weight loss, increase 0 - 5%, and increase > 5% from baseline will be evaluated.Statistical Analysis. The relationship between weight gain and some risk factors of recurrence was analyzed with cox regression and multivariate logistic regression tests. The Kaplan Meier method is used to show lifetime data.Result. Weight gain in breast cancer patients with positive Her2-negative estrogen receptor subtypes was not associated with recurrence (p = 0.264; HR 0.637; 95% CI 0.289 - 1.405). Patients with body mass index ≥ 25 kg / m2 at diagnosis had a lower risk of relapse than patients with body mass index < 25 kg / m2 (p = 0.026; HR 0.461; 95% CI, 0.234 - 0.912).Conclusions Weight gain after diagnosis in breast cancer patients with positive estrogen receptor-negative Her2 subtypes receiving hormonal therapy is not associated with recurrence.